Drug Resistance Mutations Among South African Children Living With HIV on WHO-recommended ART Regimens. (30th July 2020) - Hackett, Stephanie; Teasdale, Chloe A; Pals, Sherri; Muttiti, Anthony; Mogashoa, Mary; Chang, Joy; Zeh, Clement; Ramos, Artur; Rivadeneira, Emilia D; DeVos, Joshua; Sleeman, Katrina; Abrams, Elaine J
Abstract: Background: Children living with human immunodeficiency virus (HIV) (CLHIV) receiving antiretroviral therapy (ART) in resource-limited settings are susceptible to high rates of acquired HIV drug resistance (HIVDR), but few studies include children initiating age-appropriate World Health Organization (WHO)-recommended first-line regimens. We report data from a cohort of ART-naive South African children who initiated first-line ART. Methods: ART-eligible CLHIV aged 0–12 years were enrolled from 2012 to 2014 at 5 public South African facilities and were followed for up to 24 months. Enrolled CLHIV received standard-of-care WHO-recommended first-line ART. At the final study visit, a dried blood spot sample was obtained for viral load and genotypic resistance testing. Results: Among 72 successfully genotyped CLHIV, 49 (68.1%) received ABC/3TC/LPV/r, and 23 (31.9%) received ABC/3TC/EFV. All but 2 children on ABC/3TC/LPV/r were <3 years, and all CLHIV on ABC/3TC/EFV were ≥3 years. Overall, 80.6% (58/72) had at least one drug resistance mutation (DRM). DRMs to nonnucleoside reverse transcriptase inhibitors (NNRTIs) and nucleoside reverse transcriptase inhibitors (NRTIs) were found among 65% and 51% of all CLHIV, respectively, with no statistical difference by ART regimen. More CLHIV on ABC/3TC/EFV, 47.8% (11/23), were found to have 0 or only 1 effective antiretroviral drug remaining in their current regimen compared to 8.2% (4/49) on ABC/3TC/LPV/r. Conclusions: High levels of NNRTI and NRTI DRMs among CLHIV receiving ABC/3TC/LPV/r suggests a lasting impact of failed mother-to-child transmission interventions on DRMs. However, drug susceptibility analysis reveals that CLHIV with detectable viremia on ABC/3TC/LPV/r are more likely to have maintained at least 2 effective agents on their current HIV regimen than those on ABC/3TC/EFV. Abstract : Among a cohort of human immunodeficiency virus-positive antiretroviral therapy-naive infants and children initiating WHOrecommended first-line ABC/3TC/LPV/r and ABC/3TC/EFV, high rates of drug resistance were seen at 12–2424 months, and more children retained at least 2 effective antiretrovirals on ABC/3TC/LPV/r than those on ABC/3TC/EFV.